O custeio da aposentadoria especial e dos benefícios previdenciários decorrentes de acidentes de trabalho - Medeiros, Fabio Batista de (2009)
This paper is mainly destined to cover, with scientific accuracy, the issue of financing the special retirement plan and the social security benefits arising from work-related accidents, an issue that purely depends on the notion of risk causing the need for social security protection. The financing of the special retirement and the social security benefits arising from work-related accidents, commonly referred to as contribution for the work-related accident insurance or simply SAT , is a kind of financing of the social security, a division of the social security system. Accordingly, it features a significant importance, as it involves the inflow of revenues that allow maintaining the social security portions destined to protect the society from social contingencies caused by work, such as the risks of illnesses, disability arising from accidents and acceleration of human s natural aging process, all of which are the origin of negative influences to men s work capability. Based on that, this paper seeks to properly identify, as regards the issue, its legal nature, its constitutional grounds, its own characteristics and those possibly shared with the other segments of the Social Security Law, exploring the legal interpretation of the rules taken from Statutory Law, particularly Federal Constitution, article 22, II of Law no. 8,212/1991 and paragraphs 6 and 7 of Law no. 8,213/1991